Spatial spillover effects of financial resource allocation efficiency on green economy: Evidence from China - Ji, Xiaodong; Tang, Yixuan; Shao, Wei (Frontiers in Environmental Science, 2022)
Financial resource allocation comprises the efficiency of credit resource allocation and the savings-investment transformation rate. Based on the two aspects, the relationships between the efficiency of financial resource allocation and green economic development are empirically tested using China's panel data from 2000 to 2019 within the spatial Durbin model. The empirical results show that the efficiency of credit resource allocation in China is low, and the flow of credit resources causes a siphon effect. At the same time, the existing savings stock does not form a real credit resource. The empirical results of regional tests show that the allocation efficiency of credit resources in the eastern region is low, and negative externalities exist. The allocation efficiency of credit resources in the central and western regions has a driving effect on the development of the green economy in the region, but there also exist negative externalities. There are positive externalities in the conversion rate of savings and investment. The findings of this study indicate that China is still driving the development of the green economy through the expansion of the total financial scale. The economic benefits of improving the efficiency of financial resource allocation have not been proven.